Importance Of Awareness Of Reflective Teaching In The English Classroom In Uzbekistan - Olim Kodirov (International Journal on Integrated Education, 2023)
The article is about the importance of reflective teaching in continuous professional development of EL teachers in Uzbekistan. It also discusses reflection as a tool that encourages educators to examine their practices and outcomes critically, offers valuable insights for improving classroom management strategies. It also touches upon the conducive effect of reflection on student engagement, students’ learning styles, cultural sensitivity, language proficiency, conducive learning environment and others.